2011
DOI: 10.1515/htmp.2011.030
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Anisotropy of Creep Fracture Using Small Punch Test for Al-Al4C3 System Produced by Equal Channel Angular Pressing

Abstract: The anisotropy of the creep properties and fracture using small punch tests for the Al-Al 4 C 3 system produced by ECAP were analysed in this work. Small punch creep tests under constant force were performed at the temperature of 623 K. It was shown that the fracture results, i.e. time to fracture and deflection at fracture were different in specimens with different orientation with respect to the axis of ECAP deformation. Fracture surface analysis of the tested small punch specimens was conducted. Fractures h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The times to fracture in ECAPed material are shorter than in the hot-extruded material, though the relative difference is smaller than in the previous case of deflection rate: Assuming the same value of power F n in both materials, the time to facture is about 43 times shorter at 623 K and 14 times shorter at 723 K. The ratio at 723 K should be taken with caution since its force dependence has to be admitted. The anisotropy of the creep properties and fracture using small punch tests for the Al-Al 4 and deflection at fracture were different in specimen with different orientation with respect to the axis of ECAP deformation [30,31]. A fracture surface analysis of the tested small punch specimens was conducted.…”
Section: Mechanical Properties Of Nanostructural Systemmentioning
confidence: 99%
“…The times to fracture in ECAPed material are shorter than in the hot-extruded material, though the relative difference is smaller than in the previous case of deflection rate: Assuming the same value of power F n in both materials, the time to facture is about 43 times shorter at 623 K and 14 times shorter at 723 K. The ratio at 723 K should be taken with caution since its force dependence has to be admitted. The anisotropy of the creep properties and fracture using small punch tests for the Al-Al 4 and deflection at fracture were different in specimen with different orientation with respect to the axis of ECAP deformation [30,31]. A fracture surface analysis of the tested small punch specimens was conducted.…”
Section: Mechanical Properties Of Nanostructural Systemmentioning
confidence: 99%
“…Small punch creep tests under constant force were performed at the temperature of 623 K. It was shown that the fracture results, i.e. time to fracture and deflection at fracture were different in specimen with different orientation with respect to the axis of ECAP deformation, [26]. A fracture surface analysis of the tested small punch specimens was conducted.…”
Section: Mechanical Properties Of Nanostructural Systemmentioning
confidence: 99%